Big Jake [videorecording (DVD)] - Wayne, Michael, 1934-2003; Fink, Harry Julian; Fink, R. M. (Rita M.); Sherman, George, 1908-1991; Wayne, John, 1907-1979; Boone, Richard; Wayne, Patrick, 1939-; Mitchum, Christopher, 1943-; O'Hara, Maureen, 1920-2015 (John Wayne collection., 2005)
Big Jake McCandles, is a husband who hasn't seen his wife in over 18 years. But he returns home after his grandson is kidnapped by a vicious outlaw gang. While the law gives chase in rickety automobiles, Jake saddles up with an Indian scout and a box of money-- even though paying a ransom isn't how Jake plans to exact good old frontier justice.